A Systematic Review and Network Meta-Analysis of Biomedical Mg Alloy and Surface Coatings in Orthopedic Application - XinYue Lu; HongXin Cai; Yu Ru Li; Xinru Zheng; Jiahao Yun; Wenhui Li; XiaoYu Geng; Jae-Sung Kwon; Heng Bo Jiang (Bioinorganic Chemistry and Applications)
Magnesium alloys have great application prospects as ideal bone implant materials. However, their poor corrosion resistance limits their clinical orthopedic application. Surface modification promotes the corrosion resistance of magnesium. Conversion coatings, such as calcium phosphate (Ca-P) coating, microarc oxidation (MAO) treatment, and fluoride (FLU) treatment, have been extensively investigated in in vivo studies. This systematic review and network meta-analysis compared the influence of different conversion coatings on bone repair, material properties, and systemic host response in orthopedic applications. Using the PICOS model, the inclusion criteria for biodegradable magnesium and its alloys were determined for in vivo studies. Four databases were used. The standard and weight mean differences with 95% confidence intervals were used to analyze new bone formation and degradation rate. Network structure and forest plots were created, and ranking probabilities were estimated. The risk of bias and quality of evidence were assessed using SYRCLE, CERQual, and GRADE tools. In the qualitative analysis, 43 studies were selected, and the evaluation of each outcome indicator was not entirely consistent from article to article. In the quantitative analysis, 21 articles were subjected to network meta-analysis, with 16 articles on implant degradation and 8 articles for new bone formation. Additionally, SUCRA indicated that Ca-P coating exhibited the highest corrosion resistance, followed by FLU treatment. MAO demonstrated the best capability for new bone formation, followed by Ca-P coating. Ca-P coating exhibited the highest overall performance. To conclude, coated Mg can promote better new bone formation than bare Mg and has considerable biocompatibility. Ca-P-coated Mg and MAO-coated Mg have the greatest potential to significantly promote corrosion resistance and bone regeneration, respectively. The findings of this study will provide a theoretical basis for the investigation of composite coatings and guidance for the orthopedic application of Mg bone implants.